Anti-static composition, preparation method and application thereof, misfire anti-static putty powder and putty slurry
By modifying polypyrrole and polyaniline, combined with oxidative polymerization technology and vacuum adsorption technology, fire-free anti-static putty materials are prepared, which solves the shortcomings of existing materials in electrostatic relay and mildew prevention, and achieves better physical and chemical indicators and safety performance.
Patent Information
- Application Number
- CN202510021685.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-03-14
AI Technical Summary
The existing fire-free floor materials have shortcomings in electrostatic diversion and mildew prevention, and the construction process has added quality hazards.
Through oxidative polymerization technology and vacuum adsorption technology, polypyrrole and polyaniline are modified to form polypyrrole-diatomaceous earth-paraffinized composite phase change material and polyaniline-copper-copper zinc oxide nanohybrids, and ignition-free anti-static putty powder and putty slurry are prepared in combination with these materials.
It achieves the effect of not getting angry, anti-static and anti-mold, meets the needs of low-carbon energy-saving and safety, and can be matched with a variety of coating surface effects, improving the performance and safety of putty materials.
Smart Images

Figure BDA0005231570230000121 
Figure BDA0005231570230000131 
Figure BDA0005231570230000171
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coating materials, and in particular to an antistatic composition and a preparation method and application thereof, a non-ignitable antistatic putty powder and a putty slurry. Background Art
[0002] With the development of society, the demand for materials in various fields has shown a trend of diversification and specialization. Some special places such as military manufacturing, fireworks manufacturing, pharmaceutical factories, wineries, gas stations, chemical plants, precision electronics factories, textile factories, printing factories, sterile medical laboratories and other flammable and explosive places have special fire protection and explosion prevention requirements. In order to ensure safe production and safe operation, the fire protection and anti-static requirements for the floor and wall and other related environmental materials in such special places are very strict, and they must have certain non-flammable and anti-static properties. The so-called non-flammable property is the conversion of kinetic energy. "When the material is subjected to mechanical effects such as friction, impact or rubbing with hard objects such as metal or stone, sparks or sparks will not occur, causing the danger of flammable materials causing fire or explosion." The reason for the ignition of wall and floor materials is generally due to the accumulation of static electricity caused by mechanical impact and friction. When the external conditions are suitable, there will be hidden dangers of fire or explosion. Therefore, wall and floor materials with special fire protection requirements must have the functions of non-flammable and anti-static. With the directional focus of demand, researchers from scientific research institutions and universities around the world continue to expand their research on non-flammable materials.
[0003] At present, the research on non-flammable materials is focused on floor materials. According to the properties of the materials, they can be divided into non-flammable metal floors and non-flammable non-metal floors. Non-flammable metal floor materials are generally made of non-ferrous metals such as copper plates and aluminum plates. Non-flammable non-metal materials can be divided into non-flammable organic floor materials, such as asphalt, wood, rubber, etc., but because these materials have poor conductivity and certain insulation, they are not conducive to static electricity conduction, and it is necessary to set up electrical conduction; the other is non-flammable inorganic floor materials, which are made of inorganic materials such as concrete and terrazzo configured with non-flammable sand and gravel aggregates.
[0004] CN104211345A discloses a non-fired concrete prepared with common sand, which is prepared by mixing cementitious material cement, common sand, non-fired coarse aggregate, water, and admixtures in proportion. The cementitious material cement adopts common cement with a strength grade of 32.5 or slag cement with a strength grade of 32.5; the non-fired coarse aggregate adopts dolomite or limestone with a particle size of 10 to 20 mm; the common sand adopts fine sand with a fineness modulus of 1.6 to 2.1; the admixture is selected from one or more of a water reducer, a retarder, a plasticizer, and a composite soil adsorbent. This scheme provides a way of thinking that common sand is combined with non-fired aggregate to achieve non-fire and does not affect the material properties and mechanical properties of concrete, but there are certain requirements for the ratio of common sand to non-fired aggregate, and at this stage, with the tightening of relevant environmental protection policies, the price of common sand and non-fired machine-made sand aggregate are inverted, and the economy is no longer advantageous.
[0005] CN116903319A discloses an anti-static non-flammable wear-resistant floor material and a preparation method thereof, wherein the floor material comprises component A and component B in a mass ratio of (4-7):1, wherein component A comprises 30-45% cement, 45-55% non-flammable aggregate, 1-3% active admixture, 5-10% functional admixture, 0.5-1% special admixture and 0.1-1.2% conductive material by mass fraction, and component B is a polymer emulsion. The core of this scheme is to utilize the cross-linking of two-component materials to enhance the rigidity and flexibility of the material, and at the same time, composite conductive materials and non-flammable aggregates to achieve non-flammable and anti-static effects. This scheme increases the construction process and construction difficulty compared to single-component materials, and in actual construction, workers are very likely to add less or omit one of the components in order to save time, which increases many quality risks.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] The purpose of the present invention is to provide an antistatic composition and its preparation method and application, non-fire-resistant antistatic putty powder and putty slurry. The present invention uses oxidative polymerization technology and vacuum adsorption technology, and adopts specific modified materials to modify polypyrrole and polyaniline respectively, introduces them into the putty product system to be compatible with other raw materials, and at the same time gives better physical and chemical indicators, non-fire-resistant, antistatic and mildew-proof indicators, to obtain a non-fire-resistant antistatic interior wall mildew-proof putty, which not only meets the low-carbon energy-saving and safety requirements, but also can be matched with a variety of coating decorative effects to meet consumers' pursuit of a better home life.
[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0009] In a first aspect, the present invention provides an antistatic composition, comprising a polypyrrole-diatomaceous earth-paraffin shaping composite phase change material and a polyaniline-copper-coated zinc oxide nano-hybrid.
[0010] Preferably, the mass ratio of the polypyrrole-diatomaceous earth-paraffin shaping composite phase change material to the polyaniline-copper-coated zinc oxide nano-hybrid is (2-4):1.
[0011] Preferably, the polypyrrole-diatomaceous earth-paraffin shaping composite phase change material comprises: an inner core formed of a polypyrrole-diatomaceous earth composite material, and a coating layer formed of paraffin coating the surface of the inner core.
[0012] Preferably, the mass ratio of the polypyrrole-diatomaceous earth composite material to paraffin is (2-4):1.
[0013] Preferably, the polyaniline-copper-coated zinc oxide nano-hybrid comprises: copper-coated zinc oxide nanoparticles and polyaniline modified on the copper-coated zinc oxide nanoparticles; wherein the copper-coated zinc oxide nanoparticles comprise a zinc oxide nanoparticle core and a copper coating coated on the surface of the core.
[0014] In a second aspect, the present invention provides a method for preparing the antistatic composition according to the first aspect, the preparation method comprising the following steps:
[0015] The antistatic composition is obtained by mixing the polypyrrole-diatomaceous earth-paraffin shaping composite phase change material and the polyaniline-copper-coated zinc oxide nano hybrid.
[0016] Preferably, the polypyrrole-diatomaceous earth-paraffin shaping composite phase change material is prepared by the following steps:
[0017] (a) adding a dispersant and pyrrole to an aqueous solution of diatomaceous earth to disperse the mixture to obtain a dispersion; adding an aqueous solution of an iron salt to the dispersion to perform a polymerization reaction, and filtering, washing and drying the mixture in sequence after the reaction is completed to obtain a polypyrrole-diatomaceous earth composite material;
[0018] (b) immersing the polypyrrole-diatomaceous earth composite material obtained in step (a) into paraffin for impregnation, and filtering and drying in sequence after the impregnation is completed to obtain the polypyrrole-diatomaceous earth-paraffin shaping composite phase change material.
[0019] Preferably, in step (a), the mass ratio of the dispersant, pyrrole, diatomaceous earth and iron salt is (0.5-0.75):1:1:(3.5-5).
[0020] Preferably, in step (a), the dispersant is sodium dodecylbenzene sulfonate.
[0021] Preferably, in step (a), the iron salt is ferric chloride.
[0022] Preferably, in step (a), the dispersion is ultrasonic dispersion, the power of the ultrasonic dispersion is 300 to 500 W, and the time of the ultrasonic dispersion is 30 to 40 min.
[0023] Preferably, in step (a), the polymerization reaction temperature is -5 to 5°C, and the polymerization reaction time is 2 to 3 hours.
[0024] Preferably, in step (a), the drying temperature is 50-60° C., and the drying time is 24-36 hours.
[0025] Preferably, in step (b), the mass ratio of the polypyrrole-diatomaceous earth composite material to paraffin is (2-4):1.
[0026] Preferably, in step (b), the immersion temperature is 30-35° C., and the immersion time is 2-3 hours.
[0027] Preferably, in step (b), the drying temperature is 90-100°C.
[0028] Preferably, the polyaniline-copper-coated zinc oxide nanohybrid is prepared by the following steps:
[0029] (A) mixing and grinding a zinc source and a copper source, and then calcining to obtain copper-coated zinc oxide nanoparticles;
[0030] (B) adding the copper-coated zinc oxide nanoparticles obtained in step (B) to the solution containing aniline, then dropping a solution containing an initiator to react, and filtering and drying in sequence after the reaction is completed to obtain the polyaniline-copper-coated zinc oxide nanohybrid;
[0031] Preferably, in step (A), the molar ratio of the zinc source to the copper source is 1:(1-2).
[0032] Preferably, in step (A), the zinc source is zinc acetate.
[0033] Preferably, in step (A), the copper source is copper acetate.
[0034] Preferably, in step (A), the calcination temperature is 250-350° C., and the calcination time is 3-4 hours.
[0035] Preferably, in step (B), the molar ratio of zinc oxide, aniline and initiator is (1-2):1:1.
[0036] Preferably, in step (B), the aniline-containing solution comprises aniline and hydrochloric acid; wherein the molar ratio of aniline to hydrochloric acid is (0.02-0.03):1.
[0037] Preferably, in step (B), the initiator-containing solution comprises an initiator and hydrochloric acid; wherein the molar ratio of the initiator to the hydrochloric acid is (0.02-0.03):1.
[0038] Preferably, in step (B), the initiator is ammonium persulfate.
[0039] Preferably, in step (B), the reaction temperature is -5 to 5°C, and the reaction time is 6 to 8 hours.
[0040] Preferably, in step (B), the drying temperature is 50-60°C.
[0041] In a third aspect, the present invention provides a use of the antistatic composition as described in the first aspect in the preparation of a non-flammable interior wall decoration material.
[0042] In a fourth aspect, the present invention provides a non-inflammable antistatic putty powder, wherein the non-inflammable antistatic putty powder comprises the following components in parts by weight:
[0043] 10-20 parts of white cement
[0044] 3-5 parts of sulphoaluminate cement
[0045] Heavy calcium carbonate 50-75 parts
[0046] 10-20 copies of antistatic materials;
[0047] Wherein, the antistatic material includes the antistatic composition as described in the first aspect.
[0048] Preferably, the non-fireable antistatic putty also includes 1.2 to 1.5 parts of rubber powder.
[0049] Preferably, the rubber powder is a modified polymer redispersible rubber powder.
[0050] Preferably, the non-fireable antistatic putty also includes 0.8 to 1.5 parts of an auxiliary agent.
[0051] Preferably, the auxiliary agent includes any one of cellulose ether, silicate or water reducing agent, or a combination of at least two of them.
[0052] Preferably, the cellulose ether is hydroxypropyl methylcellulose ether.
[0053] Preferably, the silicate is selected from bentonite and / or lithium-modified magnesium aluminum silicate.
[0054] Preferably, the water reducer is a polycarboxylate water reducer.
[0055] In a fifth aspect, the present invention provides a non-flammable antistatic putty slurry, wherein the non-flammable antistatic putty slurry comprises the non-flammable antistatic putty powder as described in the fourth aspect and water.
[0056] Preferably, the mass ratio of the non-fireable antistatic putty powder to water is 1:(0.36-0.38).
[0057] Compared with the prior art, the present invention has the following beneficial effects:
[0058] There is no non-inflammable and anti-static leveling material for wall decoration materials. Polypyrrole and polyaniline are conductive polymers. Through oxidative polymerization technology and vacuum adsorption technology, the present invention uses specific materials to modify them respectively, and introduces them into the putty product system to make them compatible with other raw materials. At the same time, it is given better physical and chemical indicators and mildew resistance indicators, and a non-inflammable and anti-static interior wall mildew-proof putty is obtained, which not only meets the low-carbon energy-saving and safety needs, but also can be matched with a variety of coating decorative effects to meet consumers' pursuit of a better home life. DETAILED DESCRIPTION
[0059] Unless otherwise defined herein, scientific and technical terms used in conjunction with the present invention shall have the meanings commonly understood by those of ordinary skill in the art. The meaning and scope of the terms should be clear, however, in the case of any potential ambiguity, the definitions provided herein take precedence over any dictionary or external definitions. In this application, unless otherwise stated, the use of "or" means "and / or". In addition, the use of the term "including" and other forms is non-limiting.
[0060] It should be noted that specific details are described in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in a variety of other ways different from those described herein, and those skilled in the art can make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0061] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0062] In a first aspect, the present invention provides an antistatic composition, comprising a polypyrrole-diatomaceous earth-paraffin shaping composite phase change material and a polyaniline-copper-coated zinc oxide nano-hybrid.
[0063] Polypyrrole and polyaniline are commonly used conductive polymers, but they are usually not directly introduced into the putty product system. The present invention obtains antistatic material A (polypyrrole-diatomite-paraffin shaping composite phase change material) and antistatic material B (polyaniline-copper-coated zinc oxide nano hybrid) by modification. The introduction of diatomite in antistatic material A makes polypyrrole compatible with inorganic dry powder raw materials, and the introduction of paraffin gives the material an additional phase change energy storage effect; the introduction of copper-coated zinc oxide nanoparticles in antistatic material B improves the compatibility of polyaniline with inorganic dry powder raw materials, and gives the material an additional mildew-proof effect. The present invention adopts oxidative polymerization technology combined with non-inflammable antistatic technology, so that polypyrrole-diatomite-paraffin shaping composite phase change material and polyaniline-copper-coated zinc oxide nano hybrid cooperate with each other, synergistically enhance the effect, and jointly introduce into the putty product system to be compatible with other raw materials, while giving better physical and chemical indicators and mildew-proof indicators, further improving the effects of non-inflammability, antistatic and mildew-proof.
[0064] As an optional embodiment, the mass ratio of the polypyrrole-diatomaceous earth-paraffin shaping composite phase change material and the polyaniline-copper-coated zinc oxide nanohybrid is (2-4):1, for example, it can be 2:1, 2.2:1, 2.4:1, 2.5:1, 2.6:1, 2.8:1, 3:1, 3.2:1, 3.4:1, 3.5:1, 3.6:1, 3.8:1, 4:1, etc.
[0065] As an optional implementation, the polypyrrole-diatomaceous earth-paraffin shaping composite phase change material includes: an inner core formed of a polypyrrole-diatomaceous earth composite material, and a coating layer formed of paraffin coating the surface of the inner core.
[0066] As an optional embodiment, the mass ratio of the polypyrrole-diatomaceous earth composite material to paraffin is (2-4):1, for example, it can be 2:1, 2.5:1, 3:1, 3.5:1, 4:1, etc.
[0067] As an optional embodiment, the polyaniline-copper-coated zinc oxide nanohybrid comprises: copper-coated zinc oxide nanoparticles and polyaniline modified on the copper-coated zinc oxide nanoparticles; wherein the copper-coated zinc oxide nanoparticles comprise a zinc oxide nanoparticle core and a copper coating coated on the surface of the core.
[0068] In a second aspect, the present invention provides a method for preparing the antistatic composition according to the first aspect, the preparation method comprising the following steps:
[0069] The antistatic composition is obtained by mixing the polypyrrole-diatomaceous earth-paraffin shaping composite phase change material and the polyaniline-copper-coated zinc oxide nano hybrid.
[0070] As an optional embodiment, the polypyrrole-diatomaceous earth-paraffin shaping composite phase change material is prepared by the following steps:
[0071] (a) adding a dispersant and pyrrole to an aqueous solution of diatomaceous earth to disperse the mixture to obtain a dispersion; adding an aqueous solution of an iron salt to the dispersion to perform a polymerization reaction, and filtering, washing and drying the mixture in sequence after the reaction is completed to obtain a polypyrrole-diatomaceous earth composite material;
[0072] (b) immersing the polypyrrole-diatomaceous earth composite material obtained in step (a) into paraffin for impregnation, and filtering and drying in sequence after the impregnation is completed to obtain the polypyrrole-diatomaceous earth-paraffin shaping composite phase change material.
[0073] As an optional embodiment, in step (a), the mass ratio of the dispersant, pyrrole, diatomaceous earth and iron salt is (0.5-0.75):1:1:(3.5-5);
[0074] Here, “0.5-0.75” may be, for example, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, etc.;
[0075] Here, “3.5-5” can be, for example, 3.5, 3.75, 4, 4.25, 4.5, 4.75, 5, etc.
[0076] As an optional embodiment, in step (a), the dispersant is sodium dodecylbenzene sulfonate.
[0077] As an optional embodiment, in step (a), the iron salt is ferric chloride.
[0078] As an optional embodiment, in step (a), the dispersion is ultrasonic dispersion, the power of the ultrasonic dispersion is 300-500 W, for example, 300 W, 320 W, 340 W, 350 W, 360 W, 380 W, 400 W, 420 W, 440 W, 450 W, 460 W, 480 W, 500 W, etc., and the time of the ultrasonic dispersion is 30-40 min, for example, 30 min, 32 min, 34 min, 35 min, 36 min, 38 min, 40 min, etc.
[0079] As an optional embodiment, in step (a), the polymerization reaction temperature is -5 to 5°C, for example, -5°C, -4°C, -3°C, -2°C, -1°C, 0°C, 1°C, 2°C, 3°C, 4°C, 5°C, etc., and the polymerization reaction time is 2 to 3h, for example, 2h, 2.1h, 2.2h, 2.3h, 2.4h, 2.5h, 2.6h, 2.7h, 2.8h, 3h, etc.
[0080] As an optional embodiment, in step (a), the drying temperature is 50-60°C, for example, it can be 50°C, 52°C, 54°C, 55°C, 56°C, 58°C, 60°C, etc., and the drying time is 24-36h, for example, it can be 24h, 26h, 28h, 30h, 32h, 34h, 36h, etc.
[0081] As an optional embodiment, in step (b), the mass ratio of the polypyrrole-diatomaceous earth composite material to paraffin is (2-4):1, for example, it can be 2:1, 2.5:1, 3:1, 3.5:1, 4:1, etc.
[0082] As an optional embodiment, in step (b), the immersion temperature is 30-35°C, for example, 30°C, 31°C, 32°C, 33°C, 34°C, 35°C, etc., and the immersion time is 2-3h, for example, 2h, 2.1h, 2.2h, 2.3h, 2.4h, 2.5h, 2.6h, 2.7h, 2.8h, 3h, etc.
[0083] As an optional embodiment, in step (b), the drying temperature is 90-100°C, for example, it can be 90°C, 92°C, 94°C, 95°C, 96°C, 98°C, 100°C, etc.
[0084] As an optional embodiment, the polyaniline-copper-coated zinc oxide nanohybrid is prepared by the following steps:
[0085] (A) mixing and grinding a zinc source and a copper source, and then calcining to obtain copper-coated zinc oxide nanoparticles;
[0086] (B) adding the copper-coated zinc oxide nanoparticles obtained in step (B) to the solution containing aniline, then dropping a solution containing an initiator to react, and filtering and drying in sequence after the reaction is completed to obtain the polyaniline-copper-coated zinc oxide nanohybrid;
[0087] As an optional embodiment, in step (A), the molar ratio of the zinc source to the copper source is 1:(1-2), for example, it can be 1:1, 1:1.2, 1:1.4, 1:1.5, 1:1.6, 1:1.8, 1:2, etc.
[0088] As an optional embodiment, in step (A), the zinc source is zinc acetate.
[0089] As an optional embodiment, in step (A), the copper source is copper acetate.
[0090] As an optional embodiment, in step (A), the calcination temperature is 250-350°C, for example, it can be 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, etc., and the calcination time is 3-4h, for example, it can be 3h, 3.1h, 3.2h, 3.3h, 3.4h, 3.5h, 3.6h, 3.7h, 3.8h, 3.9h, 4h, etc.
[0091] As an optional embodiment, in step (B), the molar ratio of zinc oxide, aniline and initiator is (1-2):1:1, for example, it can be 1:1:1, 1.2:1:1, 1.4:1:1, 1.5:1:1, 1.6:1:1, 1.8:1:1, 2:1:1, etc.
[0092] As an optional embodiment, in step (B), the aniline-containing solution comprises aniline and hydrochloric acid; wherein the molar ratio of the aniline to the hydrochloric acid is (0.02-0.03):1.
[0093] As an optional embodiment, in step (B), the initiator-containing solution includes an initiator and hydrochloric acid; wherein the molar ratio of the initiator to the hydrochloric acid is (0.02-0.03):1.
[0094] As an optional embodiment, in step (B), the initiator is ammonium persulfate.
[0095] As an optional embodiment, in step (B), the reaction temperature is -5 to 5°C, for example, -5°C, -4°C, -3°C, -2°C, -1°C, 0°C, 1°C, 2°C, 3°C, 4°C, 5°C, etc., and the reaction time is 6 to 8h, for example, 6h, 6.2h, 6.4h, 6.5h, 6.6h, 6.8h, 7h, 7.2h, 7.4h, 7.5h, 7.6h, 7.8h, 8h, etc.
[0096] As an optional embodiment, in step (B), the drying temperature is 50-60°C, for example, it can be 50°C, 52°C, 54°C, 55°C, 56°C, 58°C, 60°C, etc.
[0097] In a third aspect, the present invention provides a use of the antistatic composition as described in the first aspect in the preparation of a non-flammable interior wall decoration material.
[0098] In a fourth aspect, the present invention provides a non-inflammable antistatic putty powder, wherein the non-inflammable antistatic putty powder comprises the following components in parts by weight:
[0099] 10-20 parts of white cement
[0100] 3-5 parts of sulphoaluminate cement
[0101] Heavy calcium carbonate 50-75 parts
[0102] 10-20 copies of antistatic materials;
[0103] Wherein, the antistatic material includes the antistatic composition as described in the first aspect.
[0104] As an optional embodiment, in the non-fireable antistatic putty powder, the content of white cement is 10 to 20 parts, for example, it can be 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, etc.
[0105] As an optional embodiment, in the non-fireable antistatic putty powder, the content of sulphoaluminate cement is 3 to 5 parts, for example, it can be 3 parts, 3.2 parts, 3.4 parts, 3.5 parts, 3.6 parts, 3.8 parts, 4 parts, 4.2 parts, 4.4 parts, 4.5 parts, 4.6 parts, 4.8 parts, 5 parts, etc.
[0106] As an optional embodiment, in the non-fireable antistatic putty powder, the content of heavy calcium carbonate is 50 to 75 parts, for example, it can be 50 parts, 52 parts, 54 parts, 56 parts, 58 parts, 60 parts, 62 parts, 64 parts, 66 parts, 68 parts, 70 parts, 72 parts, 74 parts, 75 parts, etc.
[0107] As an optional embodiment, in the non-ignitable antistatic putty powder, the content of the antistatic material is 10 to 20 parts, for example, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, etc. It should be noted that: if the dosage of the antistatic composition described in the first aspect is high, the strength will be affected, and if the dosage of the antistatic composition described in the first aspect is low, the antistatic and mildew-proof effects cannot be achieved.
[0108] As an optional embodiment, the non-fireable antistatic putty also includes 1.2 to 1.5 parts of rubber powder, for example, it can be 1.2 parts, 1.25 parts, 1.3 parts, 1.35 parts, 1.4 parts, 1.45 parts, 1.5 parts, etc.
[0109] As an optional implementation, the rubber powder is a modified polymer redispersible rubber powder.
[0110] As an optional embodiment, the non-fireable antistatic putty also includes 0.8 to 1.5 parts of additives, for example, 0.8 parts, 0.9 parts, 1 parts, 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts, 1.5 parts, etc.
[0111] As an optional embodiment, the auxiliary agent includes any one of cellulose ether, silicate or water reducing agent, or a combination of at least two of them.
[0112] As an optional embodiment, the cellulose ether is hydroxypropyl methylcellulose ether.
[0113] As an optional embodiment, the silicate is selected from bentonite and / or lithium-modified magnesium aluminum silicate.
[0114] As an optional embodiment, the water reducer is a polycarboxylate water reducer.
[0115] In a fifth aspect, the present invention provides a non-flammable antistatic putty slurry, wherein the non-flammable antistatic putty slurry comprises the non-flammable antistatic putty powder as described in the fourth aspect and water.
[0116] Preferably, the mass ratio of the non-fireable antistatic putty powder to water is 1:(0.36-0.38), for example, it can be 1:0.36, 1:0.365, 1:0.37, 1:0.375, 1:0.38, etc.
[0117] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.
[0118] The sources of the components in the following examples are as follows:
[0119]
[0120]
[0121] Example 1
[0122] This embodiment provides an antistatic composition, which is prepared by the following steps:
[0123] I. Preparation of polypyrrole-diatomaceous earth-paraffin shaping composite phase change material:
[0124] (a) 0.5 parts of sodium dodecylbenzene sulfonate and 1 part of pyrrole are dropped into 1 part of diatomaceous earth aqueous solution (wherein the concentration of the diatomaceous earth aqueous solution is 3g / mL), and ultrasonicated at a power of 400W for 35min until uniform dispersion (no fine oil droplets appear in the mixed liquid); under ice bath conditions, 3.5 parts of ferric chloride hexahydrate aqueous solution (wherein the purity of ferric chloride hexahydrate is 99%) are added, and stirred and polymerized under ice bath conditions for 2.5h, and a black solid product is obtained by filtering, and then the residual ferric chloride is removed by washing with a large amount of anhydrous ethanol and deionized water, and finally dried at 55°C for 30h to constant weight to obtain a polypyrrole-diatomaceous earth composite material;
[0125] (b) immersing 3 parts of the composite material into a container containing 1 part of paraffin wax, melting and impregnating at 32° C. for 2.5 hours, then removing excess paraffin wax on the surface with filter paper, and placing it in a vacuum drying oven at 95° C. to dry to constant weight, thereby obtaining the polypyrrole-diatomaceous earth-paraffin shaped composite phase change material.
[0126] II. Preparation of polyaniline-copper-coated zinc oxide nanohybrids:
[0127] (A) Zinc acetate dihydrate and copper acetate monohydrate were ground in a mortar with a pestle in a molar ratio of 1:1 and mixed evenly, and then transferred to a quartz crucible and calcined in a muffle furnace at 300°C for 3.5 hours. The mixture turned dark brown and cooled to obtain copper-coated zinc oxide nanoparticles;
[0128] (B) adding aniline to a hydrochloric acid solution (the molar ratio of aniline to hydrochloric acid is 0.025:1), stirring for 1.5 hours to obtain an aniline hydrochloric acid solution; adding ammonium persulfate to the hydrochloric acid solution (the molar ratio of ammonium persulfate to hydrochloric acid is 0.025:1), stirring for 1.5 hours to obtain an ammonium persulfate hydrochloric acid solution;
[0129] (C) The copper-coated zinc oxide nanoparticles obtained in step (A) and the aniline hydrochloric acid solution and ammonium persulfate hydrochloric acid solution obtained in step (B) are mixed in a molar ratio of zinc oxide: aniline: ammonium persulfate of 1.5:1:1, then reacted at 0° C. for 7 hours, and finally the precipitate was collected by filtration and dried to constant weight at 55° C. to obtain the polyaniline-copper-coated zinc oxide nanohybrid.
[0130] III. Preparation of antistatic composition:
[0131] The polypyrrole-diatomaceous earth-paraffin shaping composite phase change material and the polyaniline-copper-coated zinc oxide nano hybrid are uniformly mixed in a mass ratio of 3:1 to obtain the antistatic composition.
[0132] Example 2
[0133] This embodiment provides an antistatic composition, which is different from Embodiment 1 only in that the polypyrrole-diatomaceous earth-paraffin shaping composite phase change material and the polyaniline-copper-coated zinc oxide nanohybrid are mixed uniformly at a mass ratio of 2:1 to obtain the antistatic composition.
[0134] Example 3
[0135] This embodiment provides an antistatic composition, which is different from Embodiment 1 only in that the polypyrrole-diatomaceous earth-paraffin wax-fixed composite phase change material and the polyaniline-copper-coated zinc oxide nanohybrid are mixed uniformly at a mass ratio of 4:1 to obtain the antistatic composition.
[0136] Comparative Example 1
[0137] This comparative example provides an antistatic material, which is a polypyrrole-diatomaceous earth-paraffin shaping composite phase change material, and is specifically prepared by the following steps:
[0138] (a) 0.5 parts of sodium dodecylbenzene sulfonate and 1 part of pyrrole are dropped into 1 part of diatomaceous earth aqueous solution (wherein the concentration of the diatomaceous earth aqueous solution is 3g / mL), and ultrasonicated at a power of 400W for 35min until uniform dispersion (no fine oil droplets appear in the mixed liquid); under ice bath conditions, 3.5 parts of ferric chloride hexahydrate aqueous solution (wherein the purity of ferric chloride hexahydrate is 99%) are added, and stirred and polymerized under ice bath conditions for 2.5h, and a black solid product is obtained by filtering, and then the residual ferric chloride is removed by washing with a large amount of anhydrous ethanol and deionized water, and finally dried at 55°C for 30h to constant weight to obtain a polypyrrole-diatomaceous earth composite material;
[0139] (b) immersing 3 parts of the composite material into a container containing 1 part of paraffin wax, melting and impregnating at 32° C. for 2.5 hours, then removing excess paraffin wax on the surface with filter paper, and placing it in a vacuum drying oven at 95° C. to dry to constant weight, thereby obtaining the polypyrrole-diatomaceous earth-paraffin shaped composite phase change material.
[0140] Comparative Example 2
[0141] This comparative example provides an antistatic material, which is a polyaniline-copper-coated zinc oxide nanohybrid, and is specifically prepared by the following steps:
[0142] (A) Zinc acetate dihydrate and copper acetate monohydrate were ground in a mortar with a pestle in a molar ratio of 1:1 and mixed evenly, and then transferred to a quartz crucible and calcined in a muffle furnace at 300°C for 3.5 hours. The mixture turned dark brown and cooled to obtain copper-coated zinc oxide nanoparticles;
[0143] (B) adding aniline to a hydrochloric acid solution (the molar ratio of aniline to hydrochloric acid is 0.025:1), stirring for 1.5 hours to obtain an aniline hydrochloric acid solution; adding ammonium persulfate to the hydrochloric acid solution (the molar ratio of ammonium persulfate to hydrochloric acid is 0.025:1), stirring for 1.5 hours to obtain an ammonium persulfate hydrochloric acid solution;
[0144] (C) The copper-coated zinc oxide nanoparticles obtained in step (A) and the aniline hydrochloric acid solution and ammonium persulfate hydrochloric acid solution obtained in step (B) are mixed in a molar ratio of zinc oxide: aniline: ammonium persulfate of 1.5:1:1, then reacted at 0° C. for 7 hours, and finally the precipitate was collected by filtration and dried to constant weight at 55° C. to obtain the polyaniline-copper-coated zinc oxide nanohybrid.
[0145] Comparative Example 3
[0146] This comparative example provides an antistatic composition, which is prepared by the following steps:
[0147] I. Preparation of polypyrrole-diatomite composite material:
[0148] 0.5 parts of sodium dodecylbenzene sulfonate and 1 part of pyrrole were dropped into 1 part of diatomaceous earth aqueous solution (wherein the concentration of the diatomaceous earth aqueous solution was 3 g / mL), and ultrasonicated at a power of 400 W for 35 minutes until uniform dispersion (no fine oil droplets appeared in the mixed liquid); under ice bath conditions, 3.5 parts of ferric chloride hexahydrate aqueous solution (wherein the purity of ferric chloride hexahydrate was 99%) were added, and stirred and polymerized for 2.5 hours under ice bath conditions, and a black solid product was obtained by filtration. After that, the residual ferric chloride was washed with a large amount of anhydrous ethanol and deionized water to remove the residual ferric chloride, and finally dried at 55° C. for 30 hours to constant weight to obtain a polypyrrole-diatomaceous earth composite material.
[0149] II. Preparation of polyaniline-copper-coated zinc oxide nanohybrids:
[0150] (A) Zinc acetate dihydrate and copper acetate monohydrate were ground in a mortar with a pestle in a molar ratio of 1:1 and mixed evenly, and then transferred to a quartz crucible and calcined in a muffle furnace at 300°C for 3.5 hours. The mixture turned dark brown and cooled to obtain copper-coated zinc oxide nanoparticles;
[0151] (B) adding aniline to a hydrochloric acid solution (the molar ratio of aniline to hydrochloric acid is 0.025:1), stirring for 1.5 hours to obtain an aniline hydrochloric acid solution; adding ammonium persulfate to the hydrochloric acid solution (the molar ratio of ammonium persulfate to hydrochloric acid is 0.025:1), stirring for 1.5 hours to obtain an ammonium persulfate hydrochloric acid solution;
[0152] (C) The copper-coated zinc oxide nanoparticles obtained in step (A) and the aniline hydrochloric acid solution and ammonium persulfate hydrochloric acid solution obtained in step (B) are mixed in a molar ratio of zinc oxide: aniline: ammonium persulfate of 1.5:1:1, then reacted at 0° C. for 7 hours, and finally the precipitate was collected by filtration and dried to constant weight at 55° C. to obtain the polyaniline-copper-coated zinc oxide nanohybrid.
[0153] III. Preparation of antistatic composition:
[0154] The polypyrrole-diatomaceous earth composite material and the polyaniline-copper-coated zinc oxide nanohybrid are uniformly mixed in a mass ratio of 3:1 to obtain the antistatic composition.
[0155] Comparative Example 4
[0156] This comparative example provides an antistatic composition, which is prepared by the following steps:
[0157] I. Preparation of polypyrrole-diatomaceous earth-paraffin shaping composite phase change material:
[0158] (a) 0.5 parts of sodium dodecylbenzene sulfonate and 1 part of pyrrole are dropped into 1 part of diatomaceous earth aqueous solution (wherein the concentration of the diatomaceous earth aqueous solution is 3g / mL), and ultrasonicated at a power of 400W for 35min until uniform dispersion (no fine oil droplets appear in the mixed liquid); under ice bath conditions, 3.5 parts of ferric chloride hexahydrate aqueous solution (wherein the purity of ferric chloride hexahydrate is 99%) are added, and stirred and polymerized under ice bath conditions for 2.5h, and a black solid product is obtained by filtering, and then the residual ferric chloride is removed by washing with a large amount of anhydrous ethanol and deionized water, and finally dried at 55°C for 30h to constant weight to obtain a polypyrrole-diatomaceous earth composite material;
[0159] (b) immersing 3 parts of the composite material into a container containing 1 part of paraffin wax, melting and impregnating at 32°C for 2.5 hours, then removing excess paraffin wax on the surface with filter paper, and drying it in a vacuum drying oven at 95°C to constant weight to obtain the polypyrrole-diatomaceous earth-paraffin shaped composite phase change material. II. Preparation of copper-coated zinc oxide nanohybrid:
[0160] Zinc acetate dihydrate and copper acetate monohydrate were ground with a pestle in a mortar at a molar ratio of 1:1, and then transferred to a quartz crucible and calcined at 300° C. in a muffle furnace for 3.5 hours. The mixture turned dark brown and cooled to obtain copper-coated zinc oxide nanoparticles; III. Preparation of antistatic composition:
[0161] The polypyrrole-diatomaceous earth-paraffin shaping composite phase change material and the copper-coated zinc oxide nanoparticles are uniformly mixed in a mass ratio of 3:1 to obtain the antistatic composition.
[0162] Application Example 1
[0163] This application example provides a non-inflammable anti-static putty powder and a non-inflammable anti-static putty slurry;
[0164] 1. The non-ignitable antistatic putty powder comprises the following components by weight:
[0165]
[0166] Wherein, the antistatic material is the antistatic composition provided in Example 1;
[0167] Wherein, the auxiliary agent is a combination of hydroxypropyl methylcellulose ether, lithium-modified magnesium aluminum silicate and polycarboxylic acid water reducer in a mass ratio of 0.4:0.5:0.2.
[0168] II. The non-flammable antistatic putty slurry comprises the non-flammable antistatic putty powder and water; wherein the mass ratio of the non-flammable antistatic putty powder to water is 1:0.37.
[0169] Application Example 2
[0170] This application example provides a non-inflammable anti-static putty powder and a non-inflammable anti-static putty slurry;
[0171] 1. The non-ignitable antistatic putty powder comprises the following components by weight:
[0172]
[0173]
[0174] Wherein, the antistatic material is the antistatic composition provided in Example 1;
[0175] Wherein, the auxiliary agent is a combination of hydroxypropyl methylcellulose ether, lithium-modified magnesium aluminum silicate and polycarboxylic acid water reducer in a mass ratio of 0.4:0.5:0.6.
[0176] II. The non-flammable antistatic putty slurry comprises the non-flammable antistatic putty powder and water; wherein the mass ratio of the non-flammable antistatic putty powder to water is 1:0.36.
[0177] Application Example 3
[0178] This application example provides a non-inflammable anti-static putty powder and a non-inflammable anti-static putty slurry;
[0179] 1. The non-ignitable antistatic putty powder comprises the following components by weight:
[0180]
[0181] Wherein, the antistatic material is the antistatic composition provided in Example 1;
[0182] Wherein, the auxiliary agent is a combination of hydroxypropyl methylcellulose ether, lithium-modified magnesium aluminum silicate and polycarboxylic acid water reducer in a mass ratio of 0.4:0.2:0.2.
[0183] II. The non-inflammable antistatic putty slurry comprises the non-inflammable antistatic putty powder and water; wherein the mass ratio of the non-inflammable antistatic putty powder to water is 1:0.38.
[0184] Application Example 4
[0185] This application example provides a non-flammable antistatic putty powder and a non-flammable antistatic putty slurry. The only difference from Application Example 1 is that the antistatic composition provided in Example 1 is replaced by the antistatic composition provided in Example 2, and the other settings are exactly the same as Application Example 1.
[0186] Application Example 5
[0187] This application example provides a non-inflammable antistatic putty powder and a non-inflammable antistatic putty slurry. The only difference from Application Example 1 is that the antistatic composition provided in Example 1 is replaced with an antistatic composition of equal mass provided in Example 3, and the other settings are exactly the same as Application Example 1.
[0188] Comparative application example 1
[0189] This comparative application example provides a putty powder and a putty slurry;
[0190] 1. The putty powder comprises the following components by weight:
[0191]
[0192] Wherein, the auxiliary agent is a combination of hydroxypropyl methylcellulose ether, lithium-modified magnesium aluminum silicate and polycarboxylic acid water reducer in a mass ratio of 0.4:0.5:0.2.
[0193] II. The putty slurry comprises the above-mentioned putty powder and water; wherein the mass ratio of the putty powder to water is 1:0.37.
[0194] Comparative Application Example 2
[0195] This comparative application example provides a putty powder and a putty slurry, which differs from Application Example 1 only in that the antistatic composition provided in Example 1 is replaced with an antistatic material of equal mass provided in Comparative Example 1, and the other settings are exactly the same as those in Application Example 1.
[0196] Comparative Application Example 3
[0197] This comparative application example provides a putty powder and a putty slurry, which differs from Application Example 1 only in that the antistatic composition provided in Example 1 is replaced with an antistatic material of equal mass provided in Comparative Example 2, and the other settings are exactly the same as those in Application Example 1.
[0198] Comparative Application Example 4
[0199] This comparative application example provides a putty powder and a putty slurry, which differs from Application Example 1 only in that the antistatic composition provided in Example 1 is replaced with an antistatic composition of equal mass provided in Comparative Example 3, and the other settings are exactly the same as those in Application Example 1.
[0200] Comparative Application Example 5
[0201] This comparative application example provides a putty powder and a putty slurry, which differs from Application Example 1 only in that the antistatic composition provided in Example 1 is replaced with an antistatic composition of equal mass provided in Comparative Example 4, and the other settings are exactly the same as those in Application Example 1.
[0202] Test Example 1
[0203] Test samples:
[0204] The non-inflammable antistatic putty powder and the non-inflammable antistatic putty slurry provided in Application Examples 1 to 5, and the putty powder and putty slurry provided in Comparative Application Examples 1 to 5.
[0205] Test method:
[0206] The strength index performance table refers to JC / T2653-2022 and JG / T298-2010; bonding strength (standard state) and bonding strength (after immersion in water): refer to JG / T 298-2010 "Putty for Interior Use in Buildings" Type N for testing and evaluation.
[0207] The specific test results are shown in Table 1 below:
[0208] Table 1
[0209]
[0210]
[0211] As shown in Table 1 above, the 28d tensile bonding strength of the non-fireable anti-static putty prepared by adding the antistatic composition of the present invention is above 0.83MPa, the 28d compressive strength is above 21.5MPa, the 28d flexural strength is above 4.3MPa, the bonding strength under standard conditions is above 0.66MPa, and the bonding strength after immersion in water is still maintained above 0.43MPa. This shows that the non-fireable anti-static putty prepared by adding the antistatic composition of the present invention has the advantages of excellent strength index performance and good water resistance.
[0212] Test Example 2
[0213] Test samples:
[0214] The non-inflammable antistatic putty powder and the non-inflammable antistatic putty slurry provided in Application Examples 1 to 5, and the putty powder and putty slurry provided in Comparative Application Examples 1 to 5.
[0215] Test method:
[0216] JC / T2653-2022 detects non-fire performance indicators.
[0217] The specific test results are shown in Table 2 below:
[0218] Table 2
[0219]
[0220]
[0221] As shown in Table 2 above, the putty prepared by adding the antistatic composition of the present invention can maintain non-ignition within any rotation speed (600-1000r / min) and force (10-20N). This shows that the present invention uses oxidative polymerization technology and vacuum adsorption technology to modify polypyrrole and polyaniline respectively using specific modified materials, and introduces the two into the putty product system to be compatible with other raw materials, while imparting better non-ignition performance.
[0222] Test Example 3
[0223] Test samples:
[0224] The non-inflammable antistatic putty powder and the non-inflammable antistatic putty slurry provided in Application Examples 1 to 5, and the putty powder and putty slurry provided in Comparative Application Examples 1 to 5.
[0225] Test method: JC / T2653-2022 detects anti-static performance indicators.
[0226] The specific test results are shown in Table 3 below:
[0227] Table 3
[0228]
[0229]
[0230] As shown in Table 3 above, the point-to-point resistance of the putty prepared by adding the antistatic composition of the present invention is 1.2×10 6 ~1.6×10 6 Ω, surface resistance is 1.4×10 5 ~2.0×10 5 This shows that the present invention uses oxidative polymerization technology and vacuum adsorption technology to modify polypyrrole and polyaniline respectively using specific modified materials, introduces the two into the putty product system to be compatible with other raw materials, and at the same time imparts better antistatic performance.
[0231] Test Example 4
[0232] Test samples:
[0233] The non-inflammable antistatic putty powder and the non-inflammable antistatic putty slurry provided in Application Examples 1 to 5, and the putty powder and putty slurry provided in Comparative Application Examples 1 to 5.
[0234] Test method: GB / T1741-2020 paint film mildew resistance.
[0235] The specific test results are shown in Table 4 below:
[0236] Table 4
[0237]
[0238]
[0239] As shown in Table 4, mold does not grow in the putty prepared by adding the antistatic composition of the present invention. This shows that the present invention uses oxidative polymerization technology and vacuum adsorption technology to modify polypyrrole and polyaniline respectively using specific modified materials, introduces the two into the putty product system to be compatible with other raw materials, and at the same time imparts better anti-mildew performance.
[0240] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. An antistatic composition, characterized in that The antistatic composition comprises a polypyrrole-diatomaceous earth-paraffin shaping composite phase change material and a polyaniline-copper-coated zinc oxide nano hybrid.
2. The antistatic composition according to claim 1, characterized in that The mass ratio of the polypyrrole-diatomaceous earth-paraffin shaping composite phase change material and the polyaniline-copper-coated zinc oxide nanohybrid is (2-4):1; Preferably, the polypyrrole-diatomaceous earth-paraffin shaping composite phase change material comprises: an inner core formed of a polypyrrole-diatomaceous earth composite material, and a coating layer formed of paraffin coated on the surface of the inner core; Preferably, the mass ratio of the polypyrrole-diatomaceous earth composite material to paraffin is (2-4):1; Preferably, the polyaniline-copper-coated zinc oxide nano-hybrid comprises: copper-coated zinc oxide nanoparticles and polyaniline modified on the copper-coated zinc oxide nanoparticles; wherein the copper-coated zinc oxide nanoparticles comprise a zinc oxide nanoparticle core and a copper coating coated on the surface of the core.
3. A method for preparing the antistatic composition according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: The antistatic composition is obtained by mixing the polypyrrole-diatomaceous earth-paraffin shaping composite phase change material and the polyaniline-copper-coated zinc oxide nano hybrid.
4. The method for preparing the antistatic composition according to claim 3, characterized in that: The polypyrrole-diatomaceous earth-paraffin shaping composite phase change material is prepared by the following steps: (a) adding a dispersant and pyrrole to an aqueous solution of diatomaceous earth to disperse the mixture to obtain a dispersion; adding an aqueous solution of an iron salt to the dispersion to perform a polymerization reaction, and filtering, washing and drying the mixture in sequence after the reaction is completed to obtain a polypyrrole-diatomaceous earth composite material; (b) immersing the polypyrrole-diatomaceous earth composite material obtained in step (a) into paraffin for impregnation, filtering and drying in sequence after the impregnation is completed to obtain the polypyrrole-diatomaceous earth-paraffin shaped composite phase change material; Preferably, in step (a), the mass ratio of the dispersant, pyrrole, diatomaceous earth and iron salt is (0.5-0.75):1:1:(3.5-5); Preferably, in step (a), the dispersant is sodium dodecylbenzene sulfonate; Preferably, in step (a), the iron salt is ferric chloride; Preferably, in step (a), the dispersion is ultrasonic dispersion, the power of the ultrasonic dispersion is 300 to 500 W, and the time of the ultrasonic dispersion is 30 to 40 min; Preferably, in step (a), the polymerization reaction temperature is -5 to 5°C, and the polymerization reaction time is 2 to 3 hours; Preferably, in step (a), the drying temperature is 50 to 60° C., and the drying time is 24 to 36 hours; Preferably, in step (b), the mass ratio of the polypyrrole-diatomaceous earth composite material to paraffin is (2-4):1; Preferably, in step (b), the immersion temperature is 30-35° C., and the immersion time is 2-3 hours; Preferably, in step (b), the drying temperature is 90-100°C.
5. The method for preparing the antistatic composition according to claim 3, characterized in that: The polyaniline-copper-coated zinc oxide nano-hybrid is prepared by the following steps: (A) mixing and grinding a zinc source and a copper source, and then calcining to obtain copper-coated zinc oxide nanoparticles; (B) adding the copper-coated zinc oxide nanoparticles obtained in step (A) to the solution containing aniline, and then dropping a solution containing an initiator to react, and after the reaction is completed, filtering and drying in sequence to obtain the polyaniline-copper-coated zinc oxide nanohybrid; Preferably, in step (A), the molar ratio of the zinc source to the copper source is 1:(1-2); Preferably, in step (A), the zinc source is zinc acetate; Preferably, in step (A), the copper source is copper acetate; Preferably, in step (A), the calcination temperature is 250-350° C., and the calcination time is 3-4 hours; Preferably, in step (B), the molar ratio of zinc oxide, aniline and initiator is (1-2):1:1; Preferably, in step (B), the aniline-containing solution comprises aniline and hydrochloric acid; wherein the molar ratio of aniline to hydrochloric acid is (0.02-0.03):1; Preferably, in step (B), the initiator-containing solution comprises an initiator and hydrochloric acid; wherein the molar ratio of the initiator to the hydrochloric acid is (0.02-0.03):1; Preferably, in step (B), the initiator is ammonium persulfate; Preferably, in step (B), the reaction temperature is -5 to 5°C, and the reaction time is 6 to 8 hours; Preferably, in step (B), the drying temperature is 50-60°C.
6. Use of the antistatic composition according to claim 1 or 2 in the preparation of non-inflammable interior wall decoration materials.
7. A non-inflammable antistatic putty powder, characterized in that: The non-fireable antistatic putty powder comprises the following components by weight: 10-20 parts of white cement 3-5 parts of sulphoaluminate cement Heavy calcium carbonate 50-75 parts 10-20 copies of antistatic material; Wherein, the antistatic material comprises the antistatic composition as claimed in claim 1 or 2.
8. The non-inflammable antistatic putty powder according to claim 7, characterized in that: The non-inflammable antistatic putty also includes 1.2 to 1.5 parts of rubber powder; Preferably, the rubber powder is a modified polymer redispersible rubber powder; Preferably, the non-inflammable antistatic putty further comprises 0.8 to 1.5 parts of an auxiliary agent; Preferably, the auxiliary agent includes any one or a combination of at least two of cellulose ether, silicate or water reducing agent; Preferably, the cellulose ether is hydroxypropyl methyl cellulose ether; Preferably, the silicate is selected from bentonite and / or lithium-modified magnesium aluminum silicate; Preferably, the water reducer is a polycarboxylate water reducer.
9. A non-inflammable antistatic putty slurry, characterized in that: The non-flammable antistatic putty slurry comprises the non-flammable antistatic putty powder as claimed in claim 7 or 8 and water.
10. The non-inflammable antistatic putty slurry according to claim 9, characterized in that: The mass ratio of the non-fireable antistatic putty powder to water is 1:(0.36-0.38).
Citation Information
Patent Citations
Common sand prepared misfire concrete
CN104211345A